Concept of ’Central’ or ’Axial’ Atlantoaxial Instability - Goel, Atul (Nepal Journal of Neuroscience, 2021)
The atlantoaxial joint is the most mobile joint of the spine and is most liable to develop instability. Atlantoaxial instability can be identified on observation of facetal alignment on lateral profile imaging, telltale clinical and radiological evidence and by direct observation of instability by manual manipulation of bones during surgery. Central or axial atlantoaxial instability is when there is no abnormal increase in atlantodental interval on dynamic imaging and there is no dural or neural compression by the odontoid process. Understanding and appropriately treating central or axial atlantoaxial instability can have clinical implications.